THE EFFECT OF LOW IMPACT AEROBIC EXERCISE WITH ONLINE SIMULATION METHOD APPROACH TO REDUCING BLOOD GLUCOSE LEVELS IN TYPE 2 DIABETES MELLITUS - H Zulkifli; Eka Rudy Purwana; Jansen Parlaungan (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Type 2 diabetes mellitus can cause blindness, kidney failure, heart attack, stroke and lower limb amputation and premature death. Exercise is the highest stimulant in glucose absorption through transport of skeletal muscle protein. Therefore, the effect of exercise or exercise on skeletal muscle may have a role in the management of patients with type 2 diabetes. This study aimed to investigate the effectiveness of low impact aerobic exercise with online guidance on the blood glucose levels of patients with type 2 diabetes. experimental design with one group pre-post test design. Seventeen patients with diabetes mellitus were recruited using a consecutive sampling technique from the Tanjung Barat Public Health Center, Lombok Barat Regency with an age range of 20 to >65 years and diagnosed with type 2 diabetes. week, for a total of 24 training sessions. Analysis of the data used was the Wilcoxon test. Based on the Wilcoxon test results, it was found that as many as 12 respondents experienced a decrease in blood glucose levels and 5 respondents did not have differences in blood glucose levels after aerobic exercise. The significance value is 0.002 <p-value 0.05, which means that there are differences in blood glucose levels after aerobic exercise.